Anoctamin 1 controls bone resorption by coupling Cl− channel activation with RANKL-RANK signaling transduction - Sun, Weijia; Guo, Shuai; Li, Yuheng; Li, JianWei; Liu, Caizhi; Chen, Yafei; Wang, Xuzhao; Tan, Yingjun; Tian, Hua; Wang, Cheng; Du, Ruikai; Zhong, Guohui; et al. (Nature communications, 2022)
Osteoclast over-activation leads to bone loss and chloride homeostasis is fundamental importance for osteoclast function. The calcium-activated chloride channel Anoctamin 1 (also known as TMEM16A) is an important chloride channel involved in many physiological processes. However, its role in osteoclast remains unresolved. Here, we identified the existence of Anoctamin 1 in osteoclast and show that its expression positively correlates with osteoclast activity. Osteoclast-specific Anoctamin 1 knockout mice exhibit increased bone mass and decreased bone resorption. Mechanistically, Anoctamin 1 deletion increases intracellular Cl − concentration, decreases H + secretion and reduces bone resorption. Notably, Anoctamin 1 physically interacts with RANK and this interaction is dependent upon Anoctamin 1 channel activity, jointly promoting RANKL-induced downstream signaling pathways. Anoctamin 1 protein levels are substantially increased in osteoporosis patients and this closely correlates with osteoclast activity. Finally, Anoctamin 1 deletion significantly alleviates ovariectomy induced osteoporosis. These results collectively establish Anoctamin 1 as an essential regulator in osteoclast function and suggest a potential therapeutic target for osteoporosis. Osteoclast over-activation leads to bone loss and chloride homeostasis is important for osteoclast function. Here, the authors show that Anoctamin 1 controls bone resorption by coupling Cl − channel activation with RANKL-RANK signaling transduction.